1991
DOI: 10.1055/s-2008-1052083
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism in neurosurgical patients

Abstract: We report the outcome of a retrospective study on the frequency of pulmonary embolism during the hospital stay in a series of 7,250 neurosurgical patients. Of 4,500 patients who underwent surgery 25 (0.55%) developed pulmonary embolism at some point after the operation while 5 of the 2,750 patients not operated on (0.18%) developed a fatal pulmonary embolism. We analyze the general risk factors--age, sex, length of stay and paralysis of the limbs. Meningioma was the most frequent intracranial tumor to be affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…This finding is supported in many studies that when the patients being smoker or alcoholic or obese when immobilized for a long duration had a higher chance of developing DVT. [9][10][11] Literature supports the finding that the incidence of DVT is directly proportional to the duration of postoperative immobilization. 4 Most of the other risk factors were not evaluated and maybe further studies are required for the other possible risk factors.…”
Section: Discussionmentioning
confidence: 84%
“…This finding is supported in many studies that when the patients being smoker or alcoholic or obese when immobilized for a long duration had a higher chance of developing DVT. [9][10][11] Literature supports the finding that the incidence of DVT is directly proportional to the duration of postoperative immobilization. 4 Most of the other risk factors were not evaluated and maybe further studies are required for the other possible risk factors.…”
Section: Discussionmentioning
confidence: 84%
“…Hemos de señalar que, además de las complicaciones propias de la cirugía de las lesiones del tercer ventriculo, la revisión de la literatura muestra una alta frecuencia de complicaciones tromboembólicas severas en estos pacientes (ictus isquémico, infarto agudo de miocardio, TEP), registrándose estas complicaciones en 8 pacientes incluido el nuestro, con un resultado de cinco muertes en el postoperatorio inmediato por dicha causa (ver Tabla I) y otras dos a las seis y ocho semanas de la cirugía respectivamente 11,25 . Si el riesgo de embolismo pulmonar sintomático en pacientes operados de un tumor cerebral está entre un 1.1 y un 5% 1, 2,8,13,24 , en el caso del glioma cordoide se han sospechado embolismos pulmonares al menos en el 15% de los pacientes, aunque los datos no se han confirmado en la mayoría de los casos con autopsia. Si bien es cierto que en estos pacientes se dan condiciones para el aumento de fenómenos trombóticos (tratamiento esteroideo, reposo en cama prolongado, posible déficit motor focal, localización tumoral en región supratentorial/supraselar, uso de vías centrales para administración de fármacos, largo tiempo quirúrgico) 8 , estas condiciones se comparten en su mayoría con otros tumores cerebrales.…”
Section: Discussionunclassified
“…Sawaya, et al, 58 found that the incidence of DVT in patients with meningiomas, malignant glioma, and metastatic disease was 72, 60, and 20%, respectively. In studies by Missori, et al, 44 and Levi, et al, 39 these investigators also noted that meningiomas seem to carry the highest risk of DVT of all intracranial tumors, especially when the lesions are in close contact with a venous sinus.…”
Section: Biological Risk Factorsmentioning
confidence: 92%
“…37 Nevertheless, there are no studies in which the incidence of DVT in the upper extremities and the risk of PE in this patient population have been examined. Missori, et al, 44 found that in 88% of patients with pulmonary emboli the source lay in the proximal veins. Therefore, it may not be clinically necessary or efficient to scan routinely for calf-vein DVTs.…”
Section: Screening Methods For Dvtmentioning
confidence: 98%